The Role of Suku Anak Dalam (SAD) Malaria Control Efforts in Jebak Village, Jambi Province, Indonesia - Fahri, Sukmal; Ariyani, Susy (Poltekkes Kemenkes Tanjung Karang, 2025)
Malaria is a significant public health problem in various regions, especially in developing countries. Suku Anak Dalam (SAD) is a tribe that lives in the jungle by foraging for forest products. SAD always lives in the forest and carries out activities such as hunting and living in the wilderness or in the garden. This research aims to highlight the importance of strengthening the role of SAD in malaria control efforts through a sustainable and integrated approach in public health programs. This research method is an observational type with an ecological study method, a cross-sectional design was carried out by involving interviews and observational, data were analyzed using the chi-square statistical test, this study as a population is the community living in the Senami forest of Jebak village as many as 40 people as a sample and the total population, this study evaluated knowledge, attitudes, and practices of malaria control. The results show that SAD has a varied understanding of malaria, with most showing high concern for control efforts. The active involvement of SAD in counseling and the implementation of preventive practices, such as the use of mosquito nets and antimalarial drugs, has increased awareness and reduced the prevalence of this disease. However, challenges such as limited access to health resources and environmental changes that affect malaria vectors remain obstacles that must be overcome.